Pengaruh Cetakan Sillicone Rubber Dan Temperatur Tuang Lilin Terhadap Kualitas Pola Lilin Pada Investment Casting - Harrianda Hudaya; Warman Fatra; Dedy Masnur (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Investment casting method is widely used in the industry, it could produce complex and high precision products.One of the important stage in the investment is the wax pattern production, because the quality of the castproduct depends on the quality of the wax pattern. Sillicone rubber in alternative mold material has goodformability, low thermal conductivity, as well as the low cost of raw materials and the processes compared withmetal. Mold sillicone rubber and pour wax temperature varied 55 ºC, 65 ºC and 75 ºC to investigate the effectof these variables on shrinkage of linear wax patterns and volume wax pattern which expressed as percentage.The lowest average of linear shrinkage is 0.65%, which obtained at temperature 55 ºC. The lowest percentage ofvolumetric shrinkage is 7.59 %, which obtained at temperature 55 ºC.Keywords : invesment casting, mold material, wax pour temperature, shrinkage